Peranan Strategis dari the AALCO dalam Akselerasi Kerjasama Regulasi dan Penanggulangan Permasalahan Hukum dan Ekonomi untuk Penerapan the Green Finance di Indonesia berdasarkan the UNFCCC Paris Agreement - Siswanto, Carissa Amanda; Parluhutan, Dian (Neolectura, 2023)
This paper analyzes the strategic roles of the Asian African Legal Consultative Organization (AALCO) in promoting the green finance implementation in Asia and Africa, with a focus on Indonesia. The research uses normative juridical research and comparative law, employing a statute approach and conceptual approach. This paper highlights that green financing is a crucial instrument in climate change mitigation and adaptation efforts as instructed by the United Nations Framework Convention on Climate Change (UNFCCC) Paris Agreement 2015. The AALCO has taken various steps to encourage the implementation of green financing in the Asia and Africa region, including in Indonesia, such as issuing guidelines and resolutions related to green financing, collaborating with various related parties, and organizing activities to increase public awareness of green finance to support the low carbon economy. The research concludes that the AALCO could play strategic roles in encouraging the implementation of green finance in Asia and Africa, notably in Indonesia. The AALCO's roles are expected to help countries in Asia and Africa to achieve the sustainable development goals, including the 13, 16 and 17th Goals on the UN Sustainable Development Goals